Indicators of Sustainable Development in Industrializing Countries : Measuring Industrial Change in Malaysia : Linking Strategies with national Policies - 392642 Peterson, Peter J.; Ahmad Fariz Mohamed; Mazlin Mokhtar (Bangi : Penerbit Universiti Kebangsaan Malaysia, 2003)
Includes bibliographical and references